Response of leuprolide on gonadal functions of women with overt hypothyroidism: a tertiary care centre study from Uttar Pradesh, India - Srivastav, Manish; Tiwari, Alankar; Kharkwal, Nihit; Gupta, Keshav Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Hypothyroidism can cause menstrual disturbances mainly oligoanovualtory cycles and sometimes menorrhagia. It has also been seen to cause subfertility and pregnancy related complications. Various studies have been done to evaluate gonadal dysfunctions in overt hypothyroidism but very few studies are there which have done using a gonadotrophin response in that subset of patients. Present study evaluates the response of leuprolide on gonadal functions of women with overt hypothyroidism in a tertiary care centre at Meerut. Methods: In this study 50 females of age 20 to 40 years with newly diagnosed overt hypothyroidism were taken as cases and age and Body Mass Index (BMI) matched healthy females were taken as controls. Both in cases and controls, basal FSH, LH, estradiol was measured on 2nd day to 5th day of menstrual cycle. Thereafter Leuprolide 20 mcg/kg was given subcutaneously on the same day. Post leuprolide test, stimulated LH, FSH and estradiol were measured. Basal and stimulated values were compared between both groups. Results: Basal LH was significantly higher in controls (8.2±3.2 mIU/L) when compared to cases (6.45±2.75 mIU/L) with a p value 0.03(<0.05). Basal estradiol and FSH levels were found to be nearly similar and non-significant in cases and controls. No significant differences were found between stimulated mean LH and estradiol in both the groups. Leuprolide response after stimulation test was found to be sluggish in patients with overt hypothyroidism compared to normal euthyroid controls. This study is the rare one done on human subject in tertiary care centre of India, however large sample and multicentric trials are necessary before establishing the biochemical results. Conclusions: Pituitary and gonadal (ovarian) response to leuprolide was found to have impaired (decreased) in overt hypothyroidism cases. This is the first study to be done in overt hypothyroid subjects to asses both basal and stimulated gonadotropin levels.